X-Ray Diffraction and Theoretical Approach to the Molecular Structure of (E)-2-(2-(1,3-dioxoisoindolin-2-yl)-1-(3-phenyl-3-methylcyclobutyl)ethylidene) hydrazine carboxamide - Yilmaz, Betul; Saracoglu, Hanife; Caliskan, Nezihe; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Springer/Plenum Publishers, 2012)
The title molecule (I), (E)-2-(2-(1,3-dioxoisoindolin-2-yl)-1-(3-phenyl-3-methylcyclobutyl) ethylidene) hydrazine carboxamide (C22H22N4O3), was synthesized and characterized by IR spectroscopy and single-cyrstal X-ray diffraction. The compound cyrstallizes in the triclinic space group P-1. In addition, the molecular geometry, vibrational frequencies and frontier molecular orbitals analysis of the title compound in the ground state have been calculated by using the HF/6-31G(d) and B3LYP/6-31G(d) methods. Molecular electrostatic potential of the compound was also performed by the theoretical method. The compound (E)-2-(2-(1,3-dioxoisoindolin-2-yl)-1-(3-phenyl-3-methylcyclobutyl) ethylidene) hydrazine carboxamide (C22H22N4O3), was characterized by IR spectroscopy, single-cyrstal X-ray diffraction and results compared with quantum chemical calculations.
Keywords: X-ray structure determination; DFT and HF calculation; B3LYP; IR spectrum